An integrated versatile lab-on-a-chip platform for the isolation and nucleic acid-based detection of pathogens. (22nd March 2017) - Sandetskaya, Natalia; Moos, Doreen; Pötter, Harald; Seifert, Stefan; Jenerowicz, Marcin; Becker, Holger; Zilch, Christian; Kuhlmeier, Dirk
Aim: Processing of the samples in molecular diagnostics is complex and labor-intensive. An integrated and automated platform for sample preparation and nucleic acid-based detection can significantly relieve this burden for the users.Results: We present a prototype of a versatile and integrated platform for the detection of pathogens in various liquid media. We describe a proof-of-concept for the integrated isolation of bacteria, cell lysis with optional DNA extraction, DNA amplification and detection in two different reactions, loop-mediated isothermal amplification and PCR, on a single microfluidic platform.Conclusion: The platform enables the transition from large sample volume to microfluidic format. The design and open interface enable its versatile application for various nucleic acid-based assays, from simple to complex setups. Lay abstract: DNA-based detection of the pathogens in liquid samples demands many complex steps, various pieces of equipment, and experienced personnel. We developed and demonstrated a platform that can perform these steps automatically on a single instrument. This can enable molecular diagnostics in the places and situations where it was not possible before. Graphical abstract: